Linkage modes on phthaloyl/triphenylamine hybrid compounds: Multi-functional AIE luminogens, non-doped emitters and organic hosts for highly efficient solution-processed delayed fluorescence OLEDs. (February 2017) - Hu, Jia; Zhang, Xianping; Zhang, Di; Cao, Xudong; Jiang, Tao; Zhang, Xinwen; Tao, Youtian
Abstract: Two soluble AIE-TADF emitters ( m- DTPACO and p- DTPACO ), comprising hole-transporting triphenylamine and electron-transporting phthaloyl moiety, have been designed and synthesized by a simple Friedel-Crafts reaction. Through altering the linkage modes (from para - to meta -position) on the central phenyl ring of terephthaloyl or isophthaloyl, optoelectronic properties can be finely tuned for two compounds. Both m- DTPACO and p- DTPACO exhibit aggregation-induced emission and delayed fluorescecene emission characteristics, with prompt/delayed fluorescent emission life times of 2.7 ns/8.3 μs and 7.4 ns/9.6 μs, respectively. p- DTPACO shows singlet/triplet energies of 2.37/2.32 eV and solution/solid-state photoluminescence quantum yield of 2/39% compared to those of 2.59/2.38 eV and 46/75% for m- DTPACO . External quantum efficiency of 2.4 and 3.7% has been obtained in solution-processed non-doped OLEDs based on AIE-TADF sky blue m- DTPACO and green p- DTPACO luminogens, respectively. Furthermore, solution processed green TADF OLEDs with double host/dopant TADF system by using the AIE-TADF materials as the host exhibit high efficiencies of 43.5 cd A −1, 33.3 lm W −1 and 13.0% for meta -positioned m- DTPACO and 29.3 cd A −1, 25.4 lm W −1 and 9.0% for para -linked p- DTPACO, respectively. The significantly higher performance for m- DTPACO than p- DTPACO host could be ascribed to its higher singlet and triplet energy levels for more efficient energy transfer as well as more efficiently preventing reverse energy transfer from the green TADF dopant to the TADF host. Graphical abstract: Highlights: Two triphenylamine and phthaloyl hybrids have been synthesized. Optoelectronic properties could be tuned through different para - and meta -linkage. The two compounds exhibited AIE-TADF characteristics. The AIE-TADF Luminogens were used as non-doped emitters and hosts for TADF OLEDs.